Biosynthesis of novel yellow-pigmented P(3HB-co-4HB) copolymer, a naturally dyed biomaterial with antimicrobial properties by Cupriavidus Sp. - Abdullah, Amirul AI-Ashraf (Universiti Sains Malaysia, 2016)
Production of yellow-pigmented P(3HB-c0-4HB) copolymer was synthesized through one-step cultivation using Cupriavidus sp. USMAHM13 using various carbon and nitrogen sources with different concentrations.